2020
DOI: 10.1186/s13041-020-0553-1
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of supralemniscal nucleus (B9) 5-HT neuronal system in nociceptive processing: a fiber photometry study

Abstract: Nociception is important perception that has harmful influence on daily life of humans. As to main pain management system, some descending pathways are called descending antinociceptive systems (DAS). As main pathways of DAS, it is well known that dorsal raphe (B6/B7)-rostral ventromedial medulla (B3)-spinal dorsal horn includes serotonergic system. However, possible role of supralemniscal (B9) serotonin (5-HT) cell group in pain management is still open question. In this study, we measured activities of B9 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…We usedtransgenic mice carryingtTA under the control of a DBHorTPH2 promoter (DBH-tTA mice or TPH2-tTA mice, respectively) [22,23,24] (Fig. 1a);10-14-week-old male mice were usedin this experiment.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…We usedtransgenic mice carryingtTA under the control of a DBHorTPH2 promoter (DBH-tTA mice or TPH2-tTA mice, respectively) [22,23,24] (Fig. 1a);10-14-week-old male mice were usedin this experiment.…”
Section: Animalsmentioning
confidence: 99%
“…Asaforementioned, a few studies have reported that A5/A7 NA neurons are implicated in the regulation of pain management, but to the best of our knowledge, only few studies have assessed how the activities of A5/A7 NA neurons are affected by nociceptive stimuli. A ber photometry system adopting acalcium (Ca 2+ ) imaging system is an advanced tool for evaluating nociceptive signaling, as demonstrated in a recent paper focused onB9 5-HT neurons [23], A10 (ventral tegmental area, VTA)dopamine (DA) neurons [24], and A13 DA neurons [25]. Therefore, we deemed it meaningfulto assessthe activities of A5/A7 NA neurons and B2 5-HT neurons in response to acute nociceptive stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…1a). Fourteen to eighteenweek-old male mice were maintained in the laboratory under standard conditions as recently described [7]. In this study, AAV-CAG-FLEX-G-CaMP6-WPRE (serotype DJ; 1 μl/injection, 3 × 10 copies/ml) and AAV-CAG-FLEX-mCherry-WPRE (serotype DJ; 1 μl/ injection, 5 × 10 12 copies/ml) were unilaterally injected into the A13 site (from bregma − 1.94 mm, lateral + 1.06 mm, and ventral − 4.20 mm from the surface of the brain) ( Fig.…”
mentioning
confidence: 99%
“…In this study, the primary antibody used was antityrosine hydroxylase raised in rabbit (AB152, EMD Millipore., Temecula, CA, USA), which was diluted at 1:500 in phosphate-buffered saline (PBS), and the secondary antibody used was CF647 donkey anti-rabbit (20,047, Biotium, Inc., Fremont, CA, USA), which was diluted at 1:200 in PBS. We adopted a fiber photometry system and the same two acute nociceptive stimuli and two noninvasive stimuli as in our previous report [7]. In short, the blue/yellow excitation light (470 nm/590 nm) was produced by a high-power LED driver.…”
mentioning
confidence: 99%
See 1 more Smart Citation